AWAL MULA SEJARAH AGAMA BUDDHA DAN PERKEMBANGANNYA HINGGA MASUK KE INDONESIA - Nur Hayati; Zaitun Saftia; Nurainun Br Barasa; Fitriani . (Al Hikmah, 2023)
Buddhism is the oldest religion in the world, originating in India. Siddharta Gautama brought the beginning of the emergence of this religion. Without a doubt, the development of Buddhism has spread to various countries, one of which is Indonesia. However, few people and students do not know about the history of Buddhism from India to Indonesia. Therefore, this study aims to describe the early history of the emergence of Buddhism, its development, teachings, and the entry of Buddhism into Indonesia. This study uses a qualitative approach with a literature review as a research method. The results of the study show: a) the early history of the emergence of Buddhism, b) the development of Buddhism, c) the teachings of Buddhism, and d) the entry of Buddhism into Indonesia. The research results are expected to be a source or reference for several readers or other researchers related to this research topic. At the same time, this research is expected to add insight for readers regarding the teachings of Buddhism. Keywords: History of Buddhism and its Development, The teachings of Buddhism, Religious Studies